Root system architecture and shoot canopy effects drive erosion control in Napier and Vetiver grasses - Michael O. Adu; Francis Kumi; Peter B. Obour; Emmanuel Arthur; Eric Oppong Danso; Samuel Banafo; Kofi Atiah; Kwadwo K. Amoah; Paul A. Asare; Joel Asiedu; Donatus B. Angnuureng; Stephen E. Moore (Ecological Engineering, 2026)

Dynamic remodeling in lipophilic metabolites during Coffea canephora maturation: A lipidomic study - Marcos V.V. Lyrio; João V.M. de Almeida; Eric C. Gier; Samuel G. Moore; Henzo P. Salvador; Fábio L. Partelli; Facundo M. Fernández; Wanderson Romão; Eustáquio V.R. de Castro (Food Chemistry, 2026)

An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

Beneficial use of contaminated sediments: a literature review of the state of practice in Europe and North America - John Toll; Eric Hedblom; Luca Sittoni; Arjan Widjeveldt; David Moore; Clifford Firstenberg; Steven Brown; Eric Dott (Journal of Soils and Sediments, 2026)

Response of soil nutrient pools and microbiomes to recurrent wildfire disturbance and varying burn severities in a mixed conifer forest - Alejandro Gutierrez; Marie E. Kroeger; Adam Killebrew; Eric R. Moore; Rodman Linn; Adam L. Atchley; L. Turin Dickman (Applied Soil Ecology, 2026)

Soil iron oxides as geochemical filters in floodplain restorations: Key drivers, dynamics, and links to nutrients and metals - Shreeram Inamdar; Joseph George Galella; Eric R. Moore; Md Moklesur Rahman; Matthew Sena; Bisesh Joshi; Marc Peipoch; Jinjun Kan (Journal of Environmental Management, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Road Salt Impacts on Soil Properties and Permanent Nitrogen Removal Capacity of Freshwater Urban Wetlands - Md. Moklesur Rahman; Marc Peipoch; Jinjun Kan; Eric Moore; Matthew Sena; Mukta Kantak; Suparn Sharma; Chander Lekha; Shreeram P. lnamdar (Wetlands, 2026)
Freshwater urban wetlands are important ecosystems that can naturally filter and remove excess nitrogen (N) through the process of denitrification (DNF). However, anthropogenic inputs such as road salt application may affect the N removal capacity of urban wetlands by affecting the relative rates of DNF and another competing reductive process that retains N – dissimilatory nitrate reduction to ammonium (DNRA). Here, we assessed 13 roadside wetlands in urban/suburban areas of Delaware, USA to determine the effects of road salt sodium (Na + ) on soil physical, chemical, and biological properties and the rates of DNF and DNRA. Based on soil Na + concentrations, wetlands were grouped into three categories: low (Na + < 70 mg kg −1 ), medium (70 mg kg −1 < Na + < 150 mg kg −1 ) and high (Na + > 150 mg kg −1 ). Rates of DNF and DNRA ranged from 0.8 – 83 and 0.2 – 24 μg N L −1 slurry h −1 , respectively. DNF was significantly lower in high Na + category wetlands whereas DNRA did not show any significant differences. Similarly, macroaggregates and bioavailable Fe were lowest in the high Na + category, whereas concentrations of soil NH 4 + , NO 3 − , TOC, TN, and microbial metrics (biomass and nosZ and nrfA functional genes) did not reveal any consistent patterns. These findings imply that road salt Na + input exhibited mixed effects on soil properties in these wetlands. Overall, elevated Na + from road salt could undermine the N removal capacity of the roadside urban wetlands. Therefore, strategies should be implemented to reduce the application of road salt or identify effective alternatives.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Increasing Prostate Cancer Education and Screening for Black Men in Southeastern Michigan: Your Prostate, Your Health - Shane A. Tinsley; Doreen Dankerlui; Camille Romain; Wilma Ruffin; Eric Brown; Clarence Burnett; Donna Long; Karen Yacobucci; Jaye Clement; Abisola Fasakin; Biola Makinde-Odusola; Eric Williams; et al. (Journal of Cancer Education, 2025)

Effects of elevated nutrient supply on litter decomposition are robust to impacts of mammalian herbivores across diverse grasslands - Adrienne B. Keller; Elizabeth T. Borer; Christopher R. Buyarski; Elsa E. Cleland; Allison Gill; Andrew S. MacDougall; Joslin L. Moore; John W. Morgan; Rebecca L. McCulley; Anita C. Risch; Eric W. Seabloom; Justin Wright; et al. (Oecologia, 2025)
Litter decomposition is one of the largest carbon (C) fluxes in terrestrial ecosystems and links aboveground biomass to soil C pools. In grasslands, decomposition drivers have received substantial attention but the role of grassland herbivores in influencing decay rates is often ignored despite their potentially large effects on standing biomass and nutrient cycling. Recent work has demonstrated that nutrient addition increases early-stage decay and suppresses late-stage decay. Mammalian herbivores can mediate the effects of nutrient supply on biomass, suggesting herbivores may alter the effects of nutrients on decomposition, though this is largely unknown. We examined how herbivory mediates the effects of nutrient supply on long-term decomposition across 19 grassland sites of the Nutrient Network distributed experiment. At each site, a full-factorial experiment of combined nitrogen (N), phosphorus (P), and micronutrient (K) enrichment (‘control’ or ‘ + NPK’) and mammalian herbivore (> ~ 50 g) exclusion (‘unfenced’ or ‘fenced’) was carried out in a randomized block design. We hypothesized that nutrient effects on litter decomposition would be strongest where herbivores caused the greatest reductions in aboveground plant biomass (i.e., at sites with more intense herbivory). After accounting for wide variation in decomposition rates across sites, we found that, within sites, elevated nutrients increased early-stage decay and suppressed late-stage decay. In contrast, neither herbivore exclusion (i.e., fencing) nor site level changes in aboveground biomass due to herbivory altered the nutrient effects on decomposition rates. Across grasslands, our results indicate that elevated nutrient supply modifies litter decomposition rates independent of herbivore impacts.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Anthropogenic Metal Storage in Wetland Soils Across the Conterminous United States - Matthew Dietrich; Michael Dumelle; Amanda M. Nahlik; Heather E. Golden; Jay R. Christensen; Charles R. Lane; Eric M. Moore; Gabriel M. Filippelli (Wetlands, 2025)

Leveraging Whole Genomes, Mitochondrial DNA and Haploblocks to Decipher Complex Demographic Histories: An Example From a Broadly Admixed Arctic Fish - Xavier Dallaire; Eric Normandeau; Thomas Brazier; Les Harris; Michael M. Hansen; Claire Mérot; Jean‐Sébastien Moore (Molecular Ecology, 2025)
The study of phylogeography has transitioned from mitochondrial haplotypes to genome‐wide analyses, borrowing from population genomics methods along the way. Whole‐genome sequencing allows the study of both mitochondrial and nuclear DNA and provides the density of markers to investigate recombination along the genome. This level of resolution could unravel complex histories of admixture between lineages, which are commonly observed in species evolving in recently deglaciated habitats. In this study, we sequenced 1120 Arctic Char genomes from 33 populations across Canada and Greenland to characterise patterns of genetic variation and diversity, and how they are shaped by hybridisation between the Arctic and Atlantic glacial lineages. Mitochondrial genomes across the study area were predominantly of Arctic origin, except in Greenland, where we observed some Atlantic descent. Through admixture analyses and demographic inferences on nuclear markers, we identified that all Canadian populations under the 66th parallel showed introgression from the Atlantic lineage, leading to higher genetic diversity. By scanning the genome using local principal component analyses, we identified putative large low‐recombining haploblocks as local ancestry tracts from either lineage. Since haplotypes might retain different signatures of postglacial histories by sheltering sequences from recombination, we attempted to infer origins of recolonisation using whole genomes vs. ancestry tracts for the Arctic lineage. Despite limitations, we unveiled clues suggesting a complex postglacial history in Arctic Char. Overall, our study demonstrates that, even at low depth, making the most of whole‐genome sequencing by analysing several genomic compartments provides a versatile and powerful way to address phylogeographic dynamics.

Shared Dispersal Patterns but Contrasting Levels of Gene Flow in Two Anadromous Salmonids Along a Broad Subarctic Coastal Gradient - Raphaël Bouchard; Charles Babin; Eric Normandeau; Amanda Xuereb; Félix Boulanger; Angela Coxon; Sanford Diamond; Robert Fireman; John Lameboy; Natasha Louttit; George Natawapineskum; Derek Okimaw; et al. (Molecular Ecology, 2025)
Dispersal is a highly variable trait influenced by life history and ecological factors, affecting gene flow when dispersers successfully reproduce. Anadromous salmonids, with their diverse migratory strategies and ecological traits, serve as an ideal model for studying dispersal evolution, showcasing significant inter‐ and intraspecific variation. Although environmental factors like temperature likely influence dispersal propensity, their effects remain poorly documented. This study compares dispersal patterns and population structure in lake whitefish ( Coregonus clupeaformis ) and brook charr ( Salvelinus fontinalis ) along the subarctic coastline of James Bay, covering four degrees of latitude. These species differ in life history and population size, representing contrasting ends of a continuum influencing dispersal and gene flow. We hypothesised that lake whitefish, with shorter freshwater residency and potentially reduced olfactory imprinting, would disperse more frequently than brook charr. Using low‐coverage whole‐genome sequencing, we found that lake whitefish exhibited broader‐scale population structure and greater long‐distance dispersal capacity than brook charr. Surprisingly, both species showed similar dispersal rates and population differentiation levels. However, lake whitefish had effective population sizes approximately 10 times larger than brook charr, indicating that while their dispersal is common, it results in lower effective gene flow. Moreover, dispersal rates in both species were lower in the northern study area, likely due to colder temperatures, delayed ice break and shorter growing seasons. These findings yield insights into how life history and environmental variation shape dispersal evolution in migratory species.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How costly is a community benefit agreement for a private project developer? - Cameron Gunton; Eric Werker; Mark A. Moore; Sean Markey (Resources Policy, 2025)

Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

Urban wall lizards are resilient to high levels of blood lead - Maya M. Moore; Emma G. Foster; Ali Amer; Logan Fraire; Alyssa Head; Annelise Blanchette; Shala J. Hankison; Alex R. Gunderson; Eric J. Gangloff (Environmental Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Integrating animals, pasture, and crops within AusFarm for modelling mixed farming - Neville I. Herrmann; Andrew D. Moore; Eric Zurcher (Environmental Modelling & Software, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

The use of Beauveria bassiana for the control of the larger grain borer, Prostephanus truncatus, in stored maize: Semi-field trials in Ghana - Belinda Luke; Mavis A. Acheampong; Drauzio E.N. Rangel; Eric W. Cornelius; Stephen K. Asante; Jerry A. Nboyine; Vincent Y. Eziah; Ken O. Fening; Clare Storm; Nick Jessop; Victor A. Clottey; Olivier Potin; et al. (Fungal Biology, 2023)

Suitability of new and existing ambient ethylene oxide measurement techniques for cancer inhalation risk assessment - Eric John Mei; Aryiana Cemari Moore; Jennifer Kaiser (Environmental Pollution, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Removal of diclofenac by UV-B and UV-C light-emitting diodes (LEDs) driven advanced oxidation processes (AOPs): Wavelength dependence, kinetic modelling and energy consumption - Raffaella Pizzichetti; Ken Reynolds; Cristina Pablos; Cintia Casado; Eric Moore; Simon Stanley; Javier Marugán (Chemical Engineering Journal, 2023)

Conservation Genetics of Clinch Dace Chrosomus sp. cf. saylori - Rebecca Bourquin; Michael J. Moore; Donald J. Orth; Eric M. Hallerman (Fishes, 2023)
Clinch Dace (Chrosomus sp. cf. saylori) is a newly recognized and yet-undescribed species of minnow with a restricted and fragmented distribution in the upper Tennessee River basin in southwestern Virginia, USA. We collected Clinch Dace from seven streams and observed variations at nine selectively neutral microsatellite DNA loci to infer population genetic processes and identify units for conservation management. Bayesian cluster analysis showed that three of the seven surveyed populations were genetically distinct, while the other four populations showed signs of recent admixture. Estimated effective population sizes and m-ratios were low within most populations, suggesting loss of alleles due to recent genetic drift. Positive FIS values, high average individual inbreeding coefficients, and high degrees of inferred relatedness among individuals suggested that inbreeding is taking place in some populations. FST values were high, and analysis of molecular variance indicated genetic divergence among populations. These indicators suggest that Clinch Dace populations are subject to the genetic processes that are characteristic of small and isolated populations.

Plastic leachate exposure drives antibiotic resistance and virulence in marine bacterial communities - Eric J. Vlaanderen; Timothy M. Ghaly; Lisa R. Moore; Amaranta Focardi; Ian T. Paulsen; Sasha G. Tetu (Environmental Pollution, 2023)

Long‐distance migration is a major factor driving local adaptation at continental scale in Coho salmon - Quentin Rougemont; Amanda Xuereb; Xavier Dallaire; Jean‐Sébastien Moore; Eric Normandeau; Alysse Perreault‐Payette; Bérénice Bougas; Eric B. Rondeau; Ruth E. Withler; Donald M. Van Doornik; Penelope A. Crane; Kerry A. Naish; et al. (Molecular Ecology, 2023)
Inferring the genomic basis of local adaptation is a long‐standing goal of evolutionary biology. Beyond its fundamental evolutionary implications, such knowledge can guide conservation decisions for populations of conservation and management concern. Here, we investigated the genomic basis of local adaptation in the Coho salmon ( Oncorhynchus kisutch ) across its entire North American range. We hypothesized that extensive spatial variation in environmental conditions and the species’ homing behaviour may promote the establishment of local adaptation. We genotyped 7829 individuals representing 217 sampling locations at more than 100,000 high‐quality RADseq loci to investigate how recombination might affect the detection of loci putatively under selection and took advantage of the precise description of the demographic history of the species from our previous work to draw accurate population genomic inferences about local adaptation. The results indicated that genetic differentiation scans and genetic–environment association analyses were both significantly affected by variation in recombination rate as low recombination regions displayed an increased number of outliers. By taking these confounding factors into consideration, we revealed that migration distance was the primary selective factor driving local adaptation and partial parallel divergence among distant populations. Moreover, we identified several candidate single nucleotide polymorphisms associated with long‐distance migration and altitude including a gene known to be involved in adaptation to altitude in other species. The evolutionary implications of our findings are discussed along with conservation applications.

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Combining Community Wastewater Genomic Surveillance with State Clinical Surveillance: A Framework for SARS-CoV-2 Public Health Practice - Ted Smith; Rochelle H. Holm; Ray Yeager; Joseph B. Moore; Eric C. Rouchka; Kevin J. Sokoloski; Erin M. Elliott; Daymond Talley; Vaneet Arora; Sarah Moyer; Aruni Bhatnagar (Food and Environmental Virology, 2022)
This study aimed to develop a framework for combining community wastewater surveillance with state clinical surveillance for the confirmation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants within the community and to provide recommendations on how to expand on such research and apply the findings in public health responses. Wastewater samples were collected weekly from 17 geographically resolved locations in Louisville/Jefferson County, Kentucky (USA), from February 10 to December 13, 2021. Genomic surveillance and quantitative reverse transcription PCR (RT-qPCR) platforms were used to screen for SARS-CoV-2 in wastewater, and state clinical surveillance was used for confirmation. The study results highlighted an increased epidemiological value of combining community wastewater genomic surveillance and RT-qPCR with conventional case-auditing methods. The spatial scale and temporal frequency of wastewater sampling provided promising sensitivity and specificity for gaining public health screening insights about SARS-CoV-2 emergence, seeding, and spread in communities. Improved national surveillance systems are needed against future pathogens and variants, and wastewater-based genomic surveillance exhibits great potential when coupled with clinical testing. This paper presents evidence that complementary wastewater and clinical testing are cost-effectively enhanced when used in combination, as they provide a strong tool for a joint public health framework. Future pathogens of interest may be examined in either a targeted fashion or using a more global approach where all pathogens are monitored. This study has also provided novel insights developed from evidence-based public health practices.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Metabolism in the Midwest: research from the Midwest Aging Consortium at the 49th Annual Meeting of the American Aging Association - Michaela E. Murphy; Akilavalli Narasimhan; Alexis Adrian; Ankur Kumar; Cara L. Green; Carolina Soto-Palma; Chathurika Henpita; Christina Camell; Christopher S. Morrow; Chung-Yang Yeh; Claire E. Richardson; Cristal M. Hill; et al. (GeroScience, 2022)

Metabolism of key atmospheric volatile organic compounds by the marine heterotrophic bacterium Pelagibacter HTCC1062 ( SAR11 ) - Eric R. Moore; Alec J. Weaver; Edward W. Davis; Stephen J. Giovannoni; Kimberly H. Halsey (Environmental Microbiology, 2022)
Summary Plants and phytoplankton are natural sources of the volatile organic compounds (VOCs) acetone and isoprene, which are reactive and can alter atmospheric chemistry. In earlier research we reported that, when co‐cultured with a diatom, the marine bacterium Pelagibacter (strain HTCC1062; ‘SAR11 clade’) reduced the concentration of compounds tentatively identified as acetone and isoprene. In this study, experiments with Pelagibacter monocultures confirmed that these cells are capable of metabolizing acetone and isoprene at rates similar to bacterial communities in seawater and high enough to consume substantial fractions of the total marine acetone and isoprene budgets if extrapolated to global SAR11 populations. Homologues of an acetone/cyclohexanone monooxygenase were identified in the HTCC1062 genome and in the genomes of a wide variety of other abundant marine taxa, and were expressed at substantial levels ( c . 10 −4 of transcripts) across TARA oceans metatranscriptomes from ocean surface samples. The HTCC1062 genome lacks the canonical isoprene degradation pathway, suggesting an unknown alternative biochemical pathway is used by these cells for isoprene uptake. Fosmidomycin, an inhibitor of bacterial isoprenoid biosynthesis, blocked HTCC1062 growth, but the cells were rescued when isoprene was added to the culture, indicating SAR11 cells may be capable of synthesizing isoprenoid compounds from exogenous isoprene.

Niche and neutral assembly mechanisms contribute to latitudinal diversity gradients in reef fishes - Nestor E. Bosch; Thomas Wernberg; Tim J. Langlois; Dan A. Smale; Pippa J. Moore; João N. Franco; Pierre Thiriet; Eric Feunteun; Cláudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee‐Dexter; et al. (Journal of Biogeography, 2021)
Aim The influence of niche and neutral mechanisms on the assembly of ecological communities have long been debated. However, we still have a limited knowledge on their relative importance to explain patterns of diversity across latitudinal gradients (LDG). Here, we investigate the extent to which these ecological mechanisms contribute to the LDG of reef fishes. Location Eastern Atlantic Ocean. Taxon Reef‐associated ray‐finned fishes. Methods We combined abundance data across ~60° of latitude with functional trait data and phylogenetic trees. A null model approach was used to decouple the influence of taxonomic diversity (TD) on functional (FD) and phylogenetic (PD) diversity. Standardized effect sizes (SES FD and SES PD) were used to explore patterns of overdispersion, clustering and randomness. Information theoretic approaches were used to investigate the role of large‐ (temperature, geographic isolation, nitrate and net primary productivity) and local‐scale (human population and depth) drivers. We further assessed the role of demographic stochasticity and its interaction with species trophic identity and dispersal capacity. Results Taxonomic diversity peaked at ~15°–20°N, with a second mode of lower magnitude at ~45°N; a pattern that was predicted by temperature, geographic isolation and productivity. Tropical regions displayed a higher proportion of overdispersed assemblages, whilst clustering increased towards temperate regions. Phylogenetic and functional overdispersion were associated with warmer, productive and isolated regions. Demographic stochasticity also contributed largely to community assembly, independently of ecoregions, although variation was dependent on the trophic identity and body size of species. Main conclusions Niche‐based processes linking thermal and resource constraints to local coexistence mechanisms have contributed to the LDG in reef fishes. These processes do not act in isolation, stressing the importance of understanding interactions between deterministic and stochastic factors driving community structure in the face of rapid biodiversity change.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Interactions among Triatoma sanguisuga blood feeding sources, gut microbiota and Trypanosoma cruzi diversity in southern Louisiana - Eric Dumonteil; Henry Pronovost; Eli F. Bierman; Anna Sanford; Alicia Majeau; Ryan Moore; Claudia Herrera (Molecular Ecology, 2020)
Integrating how biodiversity and infectious disease dynamics are linked at multiple levels and scales is highly challenging. Chagas disease is a vector‐borne disease, with specificities of the triatomine vectors and Trypanosoma cruzi parasite life histories resulting in a complex multihost and multistrain life cycle. Here, we tested the hypothesis that T. cruzi transmission cycles are shaped by triatomine host communities and gut microbiota composition by comparing the integrated interactions of Triatoma sanguisuga in southern Louisiana with feeding hosts, T. cruzi parasite and bacterial microbiota in two habitats. Bugs were collected from resident's houses and animal shelters and analysed for genetic structure, blood feeding sources, T. cruzi parasites, and bacterial diversity by PCR amplification of specific DNA markers followed by next‐generation sequencing, in an integrative metabarcoding approach. T. sanguisuga feeding host communities appeared opportunistic and defined by host abundance in each habitat, yielding distinct parasite transmission networks among hosts. The circulation of a large diversity of T. cruzi DTUs was also detected, with TcII and TcV detected for the first time in triatomines in the US. The bacterial microbiota was highly diverse and varied significantly according to the DTU infecting the bugs, indicating specific interactions among them in the gut. Expanding such studies to multiple habitats and additional triatomine species would be key to further refine our understanding of the complex life cycles of multihost, multistrain parasites such as T. cruzi , and may lead to improved disease control strategies.

Chemistry of streams draining mined and unmined watersheds in the mountaintop mined landscape of Central Appalachia, USA - Jacqueline R. Gerson; Eric Moore; Laura C. Naslund; Jennifer Rocca; Marie Simonin (Ecology, 2020)
Mountaintop removal coal mining is the predominant form of surface mining in the Appalachian Region of the United States and leads to elevated levels of chemical constituents in streams draining mined watersheds. This data set contains measurements of water chemistry in the mountaintop mined landscape of Central Appalachia. These data were collected to determine the accumulation and transport of mercury (Hg) and selenium (Se) across environmental compartments in mountaintop mining‐impacted waters as well as the impact of mountaintop mining on the aquatic‐terrestrial subsidy. Samples were collected in summer 2017 and spring/summer 2018. Data predominantly include Se, THg, and methylmercury (MeHg) in the following environmental compartments at sites impacted and unimpacted by mountaintop removal coal mining: water, sediment, biofilm, larval cranefly, adult aquatic insects, and spiders. Additional water parameters that have been found to vary across a gradient of mountaintop mining impact (total organic carbon [TOC], total nitrogen [TN], sulfate [SO 4 ], nitrate [NO 3 ], chloride [Cl], pH, sodium [Na], potassium [K], magnesium [Mg], calcium [Ca], manganese [Mn], sulfur [S], specific conductance) were also measured. The majority of sites represented are headwater streams, although some settling ponds below valley fills are included. This data set also includes taxonomic characterization of the adult aquatic insect community as well as measurements of spider density at a subset of sites. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Pelagibacter metabolism of diatom‐derived volatile organic compounds imposes an energetic tax on photosynthetic carbon fixation - Eric R. Moore; Cleo L. Davie‐Martin; Stephen J. Giovannoni; Kimberly H. Halsey (Environmental Microbiology, 2020)
Summary Volatile organic compounds (VOCs) produced by phytoplankton are molecules with high vapor pressures that can diffuse across cell membranes into the environment, where they become public goods. VOCs likely comprise a significant component of the marine dissolved organic carbon (DOC) pool utilized by microorganisms, but they are often overlooked as growth substrates because their diffusivity imposes analytical challenges. The roles of VOCs in the growth of the photoautotrophic diatom Thalassiosira pseudonana and heterotrophic bacterium Pelagibacter sp. HTCC1062 (SAR11) were examined using co‐cultures and proton‐transfer reaction time‐of‐flight mass spectrometry. VOCs at 82 m / z values were produced in the cultures, and the concentrations of 9 of these m / z values changed in co‐culture relative to the diatom monoculture. Several of the m / z values were putatively identified, and their metabolism by HTCC1062 was confirmed by measuring ATP production. Diatom carbon fixation rates in co‐culture with HTCC1062 were 20.3% higher than the diatom monoculture. Removal of VOCs from the T. pseudonana monoculture using a hydrocarbon trap caused a similar increase in carbon fixation (18.1%). These results show that a wide range of VOCs are cycled in the environment, and the flux of VOCs from phytoplankton to bacterioplankton imposes a large and unexpected tax on phytoplankton photosynthesis.

Decadal trends and ecological shifts in backwater lakes of a large floodplain river: Upper Mississippi River - Robert M. Burdis; Steven A. DeLain; Eric M. Lund; Megan J. C. Moore; Walter A. Popp (Aquatic Sciences, 2020)

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

Projected Marine Heatwaves in the 21st Century and the Potential for Ecological Impact - Eric C. J. Oliver; Michael T. Burrows; Markus G. Donat; Alex Sen Gupta; Lisa V. Alexander; Sarah E. Perkins-Kirkpatrick; Jessica A. Benthuysen; Alistair J. Hobday; Neil J. Holbrook; Pippa J. Moore; Mads S. Thomsen; Thomas Wernberg; et al. (Frontiers in Marine Science, 2019)

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Coastal Harmful Algae Bloom Monitoring via a Sustainable, Sail-Powered Mobile Platform - Jordon S. Beckler; Ethan Arutunian; Tim Moore; Bob Currier; Eric Milbrandt; Scott Duncan (Frontiers in Marine Science, 2019)

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

Self-initiated continuation of and adherence to HIV pre-exposure prophylaxis (PrEP) after PrEP demonstration project roll-off in men who have sex with men: associations with risky decision making, impulsivity/disinhibition, and sensation seeking - Martin Hoenigl; Erin Morgan; Donald Franklin; Peter L. Anderson; Elizabeth Pasipanodya; Matthew Dawson; Marvin Hanashiro; Eric E. Ellorin; Jill Blumenthal; Robert Heaton; David J. Moore; Sheldon R. Morris (Journal of NeuroVirology, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Disentangling latitudinal diversity gradients in Taxonomic, Phylogenetic, and Functional diversity of Atlantic reef fishes - Nestor Bosch; Thomas Wernberg; Timothy Langlois; Dan Smale; Pippa Moore; João Franco; Pierre Thiriet; Eric Feunteun; Claudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee-Dexter; et al. (Frontiers in Marine Science, 2019)

Geographical CO 2 sensitivity of phytoplankton correlates with ocean buffer capacity - Sophie Richier; Eric P. Achterberg; Matthew P. Humphreys; Alex J. Poulton; David J. Suggett; Toby Tyrrell; Christopher Mark Moore (Global Change Biology, 2018)
Accumulation of anthropogenic CO 2 is significantly altering ocean chemistry. A range of biological impacts resulting from this oceanic CO 2 accumulation are emerging, however, the mechanisms responsible for observed differential susceptibility between organisms and across environmental settings remain obscure. A primary consequence of increased oceanic CO 2 uptake is a decrease in the carbonate system buffer capacity, which characterizes the system's chemical resilience to changes in CO 2 , generating the potential for enhanced variability in p CO 2 and the concentration of carbonate [ ], bicarbonate [ ], and protons [H + ] in the future ocean. We conducted a meta‐analysis of 17 shipboard manipulation experiments performed across three distinct geographical regions that encompassed a wide range of environmental conditions from European temperate seas to Arctic and Southern oceans. These data demonstrated a correlation between the magnitude of natural phytoplankton community biological responses to short‐term CO 2 changes and variability in the local buffer capacity across ocean basin scales. Specifically, short‐term suppression of small phytoplankton ( p CO 2 within experiments performed in regions with higher ambient buffer capacity. The results further highlight the relevance of phytoplankton cell size for the impacts of enhanced p CO 2 in both the modern and future ocean. Specifically, cell size‐related acclimation and adaptation to regional environmental variability, as characterized by buffer capacity, likely influences interactions between primary producers and carbonate chemistry over a range of spatio‐temporal scales.

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Categorizing and Naming Marine Heatwaves - Alistair Hobday; Eric Oliver; Alex Sen Gupta; Jessica Benthuysen; Michael Burrows; Markus Donat; Neil Holbrook; Pippa Moore; Mads Thomsen; Thomas Wernberg; Dan Smale (Oceanography, 2018)

Regulation of Pain and Itch by TRP Channels - Carlene Moore; Rupali Gupta; Sven-Eric Jordt; Yong Chen; Wolfgang B. Liedtke (Neuroscience Bulletin, 2018)

Sex matters in massive parallel sequencing: Evidence for biases in genetic parameter estimation and investigation of sex determination systems - Laura Benestan; Jean‐Sébastien Moore; Ben J. G. Sutherland; Jérémy Le Luyer; Halim Maaroufi; Clément Rougeux; Eric Normandeau; Nathan Rycroft; Jelle Atema; Les N. Harris; Ross F. Tallman; Spencer J. Greenwood; et al. (Molecular Ecology, 2017)
Using massively parallel sequencing data from two species with different life history traits, American lobster ( Homarus americanus ) and Arctic Char ( Salvelinus alpinus ), we highlight how an unbalanced sex ratio in the samples and a few sex‐linked markers may lead to false interpretations of population structure and thus to potentially erroneous management recommendations. Here, multivariate analyses revealed two genetic clusters separating samples by sex instead of by expected spatial variation: inshore and offshore locations in lobster, or east and west locations in Arctic Char. To further investigate this, we created several subsamples artificially varying the sex ratio in the inshore/offshore and east/west groups and then demonstrated that significant genetic differentiation could be observed despite panmixia in lobster, and that F ST values were overestimated in Arctic Char. This pattern was due to 12 and 94 sex‐linked markers driving differentiation for lobster and Arctic Char, respectively. Removing sex‐linked markers led to nonsignificant genetic structure in lobster and a more accurate estimation of F ST in Arctic Char. The locations of these markers and putative identities of genes containing or nearby the markers were determined using available transcriptomic and genomic data, and this provided new information related to sex determination in both species. Given that only 9.6% of all marine/diadromous population genomic studies to date have reported sex information, we urge researchers to collect and consider individual sex information. Sex information is therefore relevant for avoiding unexpected biases due to sex‐linked markers as well as for improving our knowledge of sex determination systems in nonmodel species.

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Post‐glacial recolonization of the North American Arctic by Arctic char ( Salvelinus alpinus ): genetic evidence of multiple northern refugia and hybridization between glacial lineages - Jean‐Sébastien Moore; Robert Bajno; James D. Reist; Eric B. Taylor (Journal of Biogeography, 2015)
Aims We investigated post‐glacial recolonization of the North American Arctic by Arctic char ( Salvelinus alpinus ) and examined potential hybridization between different glacial lineages upon secondary contact. Location North American Arctic and adjacent areas. Methods We collected mt DNA sequence data from 1355 individuals from 110 sampling locations and data from nine microsatellite loci from 931 individuals from 37 locations. We assessed the phylogenetic relationships and geographical distribution of mt DNA haplotypes and conducted historical demographic analyses. We used a Bayesian clustering analysis method to detect potential hybridization between glacial lineages. Results Two highly divergent mt DNA lineages were identified in the Arctic region with distinct but overlapping geographic distributions: one in Beringia and the other over the entire Arctic Archipelago and coastal mainland east of Alaska. The microsatellite data also implied the existence of these two lineages. Evidence of hybridization was detected between the Arctic lineage and an Atlantic lineage in eastern North America. Main conclusions Our data suggested survival and recolonization from two northern glacial refugia: one in Beringia and another in a smaller refugium, perhaps in the Arctic Archipelago itself or a separate refugium within Beringia. Patterns of hybridization detected supported the presence of a secondary contact zone between glacial lineages in the eastern Canadian Arctic.

Using SWAT for sub-field identification of phosphorus critical source areas in a saturation excess runoff region - Michael F. Winchell; Solomon Folle; Donald Meals; Julie Moore; Raghavan Srinivasan; Eric A. Howe (Hydrological Sciences Journal, 2015)

Enhanced diversity and aflatoxigenicity in interspecific hybrids of Aspergillus flavus and Aspergillus parasiticus - Rodrigo A. Olarte; Carolyn J. Worthington; Bruce W. Horn; Geromy G. Moore; Rakhi Singh; James T. Monacell; Joe W. Dorner; Eric A. Stone; De‐Yu Xie; Ignazio Carbone (Molecular Ecology, 2015)
Aspergillus flavus and A. parasiticus are the two most important aflatoxin‐producing fungi responsible for the contamination of agricultural commodities worldwide. Both species are heterothallic and undergo sexual reproduction in laboratory crosses. Here we examine the possibility of interspecific matings between A. flavus and A. parasiticus . These species can be distinguished morphologically and genetically, as well as by their mycotoxin profiles. Aspergillus flavus produces both B aflatoxins and cyclopiazonic acid ( CPA ), B aflatoxins or CPA alone, or neither mycotoxin; Aspergillus parasiticus produces B and G aflatoxins or the aflatoxin precursor O ‐methylsterigmatocystin, but not CPA . Only four of forty‐five attempted interspecific crosses between opposite mating types of A. flavus and A. parasiticus were fertile and produced viable ascospores. Single ascospore strains from each cross were shown to be recombinant hybrids using multilocus genotyping and array comparative genome hybridization. Conidia of parents and their hybrid progeny were haploid and predominantly monokaryons and dikaryons based on flow cytometry. Multilocus phylogenetic inference showed that experimental hybrid progeny were grouped with naturally occurring A. flavus L strain and A. parasiticus . Higher total aflatoxin concentrations in some F1 progeny strains compared to midpoint parent aflatoxin levels indicate synergism in aflatoxin production; moreover, three progeny strains synthesized G aflatoxins that were not produced by the parents, and there was evidence of allopolyploidization in one strain. These results suggest that hybridization is an important diversifying force resulting in the genesis of novel toxin profiles in these agriculturally important fungi.

Association of mitochondrial DNA levels with frailty and all-cause mortality - Foram N. Ashar; Anna Moes; Ann Z. Moore; Megan L. Grove; Paulo H. M. Chaves; Josef Coresh; Anne B. Newman; Amy M. Matteini; Karen Bandeen-Roche; Eric Boerwinkle; Jeremy D. Walston; Dan E. Arking (Journal of Molecular Medicine, 2015)

Comparative migratory behavior and survival of wild and hatchery steelhead (Oncorhynchus mykiss) smolts in riverine, estuarine, and marine habitats of Puget Sound, Washington - Fred A. Goetz; Eric Jeanes; Megan E. Moore; Thomas P. Quinn (Environmental Biology of Fishes, 2015)

Mapping migration in a songbird using high‐resolution genetic markers - Kristen C. Ruegg; Eric C. Anderson; Kristina L. Paxton; Vanessa Apkenas; Sirena Lao; Rodney B. Siegel; David F. DeSante; Frank Moore; Thomas B. Smith (Molecular Ecology, 2014)
Neotropic migratory birds are declining across the W estern H emisphere, but conservation efforts have been hampered by the inability to assess where migrants are most limited—the breeding grounds, migratory stopover sites or wintering areas. A major challenge has been the lack of an efficient, reliable and broadly applicable method for measuring the strength of migratory connections between populations across the annual cycle. Here, we show how high‐resolution genetic markers can be used to identify genetically distinct groups of a migratory bird, the W ilson's warbler ( C ardellina pusilla ), at fine enough spatial scales to facilitate assessing regional drivers of demographic trends. By screening 1626 samples using 96 highly divergent single nucleotide polymorphisms selected from a large pool of candidates (~450 000), we identify novel region‐specific migratory routes and timetables of migration along the P acific F lyway. Our results illustrate that high‐resolution genetic markers are more reliable, precise and amenable to high throughput screening than previously described intrinsic marking techniques, making them broadly applicable to large‐scale monitoring and conservation of migratory organisms.

Geographic influences on fine-scale, hierarchical population structure in northern Canadian populations of anadromous Arctic Char (Salvelinus alpinus) - Les N. Harris; Jean-Sébastien Moore; Paul Galpern; Ross F. Tallman; Eric B. Taylor (Environmental Biology of Fishes, 2014)

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Arabinose-rich polymers as an evolutionary strategy to plasticize resurrection plant cell walls against desiccation - John P. Moore; Eric E. Nguema-Ona; Mäite Vicré-Gibouin; Iben Sørensen; William G.T. Willats; Azeddine Driouich; Jill M. Farrant (Planta, 2013)

Spatial and temporal development of phytoplankton iron stress in relation to bloom dynamics in the high‐latitude North Atlantic Ocean - Thomas J. Ryan-Keogh; Anna I. Macey; Maria C. Nielsdóttir; Michael I. Lucas; Sebastian S. Steigenberger; Mark C. Stinchcombe; Eric P. Achterberg; Thomas S. Bibby; C. Mark Moore (Limnology and Oceanography, 2013)
The high‐latitude North Atlantic (HLNA) is characterized by a marked seasonal phytoplankton bloom, which removes the majority of surface macronutrients. However, incomplete nitrate depletion is frequently observed during summer in the region, potentially reflecting the seasonal development of an iron (Fe) limited phytoplankton community. In order to investigate the seasonal development and spatial extent of iron stress in the HLNA, nutrient addition experiments were performed during the spring (May) and late summer (July and August) of 2010. Grow‐out experiments (48–120 h) confirmed the potential for iron limitation in the region. Short‐term (24 h) incubations further enabled high spatial coverage and mapping of phytoplankton physiological responses to iron addition. The difference in the apparent maximal photochemical yield of photosystem II (PSII) (F v : F m ) between nutrient (iron) amended and control treatments (Δ(F v : F m )) was used as a measure of the relative degree of iron stress. The combined observations indicated variability in the seasonal cycle of iron stress between different regions of the Irminger and Iceland Basins of the HLNA, related to the timing of the annual bloom cycle in contrasting biogeochemical provinces. Phytoplankton iron stress developed during the transition from the prebloom to peak bloom conditions in the HLNA and was more severe for larger cells. Subsequently, iron stress was reduced in regions where macronutrients were depleted following the bloom. Iron availability plays a significant role in the biogeochemistry of the HLNA, potentially lowering the efficiency of one of the strongest biological carbon pumps in the ocean.

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Hepatic P450 Enzyme Activity, Tissue Morphology and Histology of Mink (Mustela vison) Exposed to Polychlorinated Dibenzofurans - Jeremy N. Moore; John L. Newsted; Markus Hecker; Matthew J. Zwiernik; Scott D. Fitzgerald; Denise P. Kay; Xiaowei Zhang; Eric B. Higley; Lesa L. Aylward; Kerrie J. Beckett; Robert A. Budinsky; Steven J. Bursian; et al. (Archives of Environmental Contamination and Toxicology, 2009)

Improving Bayesian isotope mixing models: a response to Jackson et al. (2009) - Brice X. Semmens; Jonathan W. Moore; Eric J. Ward (Ecology Letters, 2009)
We recently described a Bayesian framework for stable isotope mixing models and provided a software tool, MixSIR, for conducting such analyses ( Ecol . Lett ., 2008; 11 :470). Jackson et al . ( Ecol. Lett. , 2009; 12:E1) criticized the performance of our software based on tests using simulated data. However, their simulation data were flawed, rendering claims of erroneous behaviour inaccurate. A re‐evaluation of the MixSIR source code did, however, uncover two minor coding errors, which we have fixed. When data are correctly simulated according to eqns (1)–(4) in Jackson et al. (2009) , MixSIR consistently and accurately estimated the proportional contribution of prey to a predator diet, and was surprisingly robust to additional unquantified error. Jackson et al. (2009) also suggested we use a Dirichlet prior on the source proportion parameters, which we agree with. Finally, Jackson et al. (2009) propose adding additional error parameters to our mixing model framework. We caution that such increases in model complexity should be evaluated based on data support.

Recent Origin of Dioecious and Gynodioecious Y Chromosomes in Papaya - Qingyi Yu; Rafael Navajas-Pérez; Eric Tong; Jon Robertson; Paul H. Moore; Andrew H. Paterson; Ray Ming (Tropical Plant Biology, 2008)

Relative influence of nitrogen and phosphorous availability on phytoplankton physiology and productivity in the oligotrophic sub‐tropical North Atlantic Ocean - C. Mark Moore; Matthew M. Mills; Rebecca Langlois; Angela Milne; Eric P. Achterberg; Julie La Roche; Richard J. Geider (Limnology and Oceanography, 2008)
Nutrient addition bioassay experiments were performed in the low‐nutrient, low‐chlorophyll oligotrophic subtropical North Atlantic Ocean to investigate the influence of nitrogen (N), phosphorus (P), and/or iron (Fe) on phytoplankton physiology and the limitation of primary productivity or picophytoplankton biomass. Additions of N alone resulted in 1.5‐2 fold increases in primary productivity and chlorophyll after 48 h, with larger (~threefold) increases observed for the addition of P in combination with N (NP). Measurements of cellular chlorophyll contents permitted evaluation of the physiological response of the photosynthetic apparatus to N and P additions in three picophytoplankton groups. In both Prochlorococcus and the picoeukaryotes, cellular chlorophyll increased by similar amounts in N and NP treatments relative to all other treatments, suggesting that pigment synthesis was N limited. In contrast, the increase of cellular chlorophyll was greater in NP than in N treatments in Synechococcus , suggestive of NP co‐limitation. Relative increases in cellular nucleic acid were also only observed in Synechococcus for NP treatments, indicating co‐limitation of net nucleic acid synthesis. A lack of response to relief of nutrient stress for the efficiency of photosystem II photochemistry, F v :F m , suggests that the low nutrient supply to this region resulted in a condition of balanced nutrient limited growth, rather than starvation. N thus appears to be the proximal (i.e. direct physiological) limiting nutrient in the oligotrophic sub‐tropical North Atlantic. In addition, some major picophytoplankton groups, as well as overall autotrophic community biomass, appears to be co‐limited by N and P.

Efficacy of Vegetated Buffers in Preventing Transport of Fecal Coliform Bacteria from Pasturelands - Timothy J. Sullivan; James A. Moore; David R. Thomas; Eric Mallery; Kai U. Snyder; Mark Wustenberg; Judith Wustenberg; Sam D. Mackey; Deian L. Moore (Environmental Management, 2007)

Iron limits primary productivity during spring bloom development in the central North Atlantic - C. MARK MOORE; MATTHEW M. MILLS; ANGELA MILNE; REBECCA LANGLOIS; ERIC P. ACHTERBERG; KARIN LOCHTE; RICHARD J. GEIDER; JULIE LA ROCHE (Global Change Biology, 2006)
We present in situ biophysical measurements and bioassay experiments that demonstrate iron limitation of primary productivity during the spring bloom in the central North Atlantic. Mass balance calculations indicate that nitrate drawdown is iron (Fe)‐limited and that aeolian Fe supply to this region cannot support maximal phytoplankton growth during the bloom. Using a simple simulation model, we show that relief of Fe limitation during the spring bloom can increase nitrate drawdown and, hence, new primary production, by 70%. We conclude that the episodic nature of iron supplied by dust deposition is an important factor controlling the dynamics of the spring bloom. From this, we hypothesize that variability in the timing and magnitude of the spring bloom in response to aeolian Fe supply will affect carbon drawdown and food web dynamics in the central North Atlantic.

Detritus, trophic dynamics and biodiversity - John C. Moore; Eric L. Berlow; David C. Coleman; Peter C. de Ruiter; Quan Dong; Alan Hastings; Nancy Collins Johnson; Kevin S. McCann; Kim Melville; Peter J. Morin; Knute Nadelhoffer; Amy D. Rosemond; et al. (Ecology Letters, 2004)
Traditional approaches to the study of food webs emphasize the transfer of local primary productivity in the form of living plant organic matter across trophic levels. However, dead organic matter, or detritus, a common feature of most ecosystems plays a frequently overlooked role as a dynamic heterogeneous resource and habitat for many species. We develop an integrative framework for understanding the impact of detritus that emphasizes the ontogeny and heterogeneity of detritus and the various ways that explicit inclusion of detrital dynamics alters generalizations about the structure and functioning of food webs. Through its influences on food web composition and dynamics, detritus often increases system stability and persistence, having substantial effects on trophic structure and biodiversity. Inclusion of detrital heterogeneity in models of food web dynamics is an essential new direction for ecological research.

Human PRRX1 and PRRX2 genes: cloning, expression, genomic localization, and exclusion as disease genes for Nager syndrome - Russell A. Norris; Karen K. Scott; Clara S. Moore; Gail Stetten; Cuyler R. Brown; Ethylin Wang Jabs; Eric A. Wulfsberg; Jack Yu; Michael J. Kern (Mammalian Genome, 2000)

NIPF Landowners' View of Regulation - Rebecca L. Johnson; Ralph J. Alig; Eric Moore; Robert J. Moulton (Journal of Forestry, 1997)